2014
DOI: 10.1016/j.ejor.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Integrating stochastic time-dependent travel speed in solution methods for the dynamic dial-a-ride problem

Abstract: HighlightsExtensions to four metaheuristics to handle stochastic time-dependent travel speeds.Using a state-of-the-art, network-consistent, time-dependent travel time layer.A new scheduling algorithm for the dynamic DARP with time-dependent travel speeds.Exploiting historical accident information is beneficial in certain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…For example, Figliozzi [13], [14] expressed the travel time on links as a function of the departure time which is calculated by constant or time dependent travel speed. Schilde et al [37] explored a dynamic dial-a-ride problem with stochastic time dependent travel speed. From the history data, they estimated the distribution of transportation requests by Poisson distribution, and the time between the request and the latest vehicle arrival time by Gamma distribution derived from the distribution of travel speeds and travel times.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Figliozzi [13], [14] expressed the travel time on links as a function of the departure time which is calculated by constant or time dependent travel speed. Schilde et al [37] explored a dynamic dial-a-ride problem with stochastic time dependent travel speed. From the history data, they estimated the distribution of transportation requests by Poisson distribution, and the time between the request and the latest vehicle arrival time by Gamma distribution derived from the distribution of travel speeds and travel times.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Schilde et al . presented metaheuristic based solution approaches for dynamic dial‐a‐ride problem in a road network with stochastic and time dependent travel speeds.…”
Section: Related Literaturementioning
confidence: 99%
“…Xiang et al [14] developed an approach for scheduling dial-a-ride system in a city road network with time dependent and stochastic delays. Schilde et al [15] presented metaheuristic based solution approaches for dynamic dial-a-ride problem in a road network with stochastic and time dependent travel speeds.…”
Section: Related Literaturementioning
confidence: 99%
“…The numerical results showed that the deterministic annealing algorithm is capable of obtaining better solutions for large scale instances under the acceptable computational time. Schilde et al [35] proposed four meta-heuristic methods including the dynamic VNS, the dynamic stochastic VNS, the multiple plan approach and the multiple scenario approach for dynamic DARP with consideration of the time-dependent travel speed. The block scheduling algorithm was applied to deal with time-dependent travel speeds.…”
Section: Heuristic Approachmentioning
confidence: 99%
“…Let A i,k ∈ {1, …, K}, i ∈ N be a notation which represents that request i has k alternatives (vehicle routes) that it can be inserted in, and satisfies the condition Δf i;A i;k ≤ Δf i;A i;k ' ; k ≤ k ′ ; i ∈ N . Compared with the basic greedy insertion heuristic, the Regret-K insertion heuristic selects the request to insert into the vehicle route according to Equation (35).…”
Section: Variablesmentioning
confidence: 99%